ANALISIS KEPUASAN PENGGUNA WEBSITE RENCANA PEMBELAJARAN SEMESTER DENGAN METODE END USER COMPUTING SATISFACTION - Edy Subowo; Alfa Yuliana Dewi; Riza Fahlevi; Niar Ajeng (Hexagon Jurnal Teknik dan Sains, 2022)
The Semester Learning Plan Preparation Website (RPS) is an effort of the Faculty of Engineering and Computer Science to provide tools that can be used to make the right RPS in accordance with the rules and guidelines for preparation that have been determined by the Pekajangan Muhammadiyah University. To find out user satisfaction on the website, research is needed to see the level of user satisfaction and what factors have an influence on user satisfaction itself. This study uses the End User Computing Satisfaction (EUCS) model by distributing questionnaires to get feedback from system users, which will then be processed to determine user satisfaction status. Based on the results of data processing, it was found that website users were quite satisfied (77.1%), satisfied (14%), and very satisfied 8.7%. The researcher concludes that the system performance is quite helpful and in accordance with user expectations. The level of system user satisfaction is currently at a pretty good predicate